Are Octogenarians With End-Stage Renal Disease Candidates for Renal Transplantation?. Issue 12 (December 2016) - Lønning, Kjersti; Midtvedt, Karsten; Leivestad, Torbjørn; Reisæter, Anna V.; Line, Pål-Dag; Hartmann, Anders; Heldal, Kristian
Abstract : Background: Elderly patients are the fastest-growing group in need of renal transplantation. This study puts focus on renal transplant recipients in their 80th year or longer at time of engraftment. Is there evidence to support an absolute upper age limit for renal transplantation? Methods: Recipients in their 80th year or longer, transplanted between 1983 and 2015, were included. Data were retrieved from the Norwegian Renal Registry in the end of October 2015. Graft and patient survivals were compared with recipients aged 70 to 79 years at transplantation. Results: Forty-seven patients older than 79 years were transplanted in the defined period. Median age 80.1 years, 81% were men. Median time on dialysis before transplantation was 18.5 months. All patients received an allograft from a deceased donor (median donor age, 61.8 years). In the death-censored graft survival model, there was no statistical difference between the groups. We found improved patient and graft survivals after introduction of mycophenolate mofetil and induction with basiliximab. Patients transplanted before 2000 had increased risk of death compared with those transplanted after 2000 (hazard ratio, 3.2; 95% confidence interval, 1.2-8.7). Median uncensored graft survival for patients transplanted after the year 2000 was 5.0 year (95% confidence interval, 2.4-7.6). Median patient survival was 5.0 years (3.1-6.9) and 5-year patient survival was 55%. Conclusions: Age by itself should not be an absolute contraindication against renal transplantation. An estimated 5-year survival rate of 55% post-engraftment for an 80-year-old patient is in our opinion more than acceptable. Abstract : The authors reveal an estimated 5 years survival rate of 55% postengraftment for an 80 years old patient with end-stage renal disease. In carefully selected octogenarians, kidney transplantation has an acceptable estimated 5 years survival rate in their opinion.